2010
DOI: 10.4103/0972-3919.63598
|View full text |Cite
|
Sign up to set email alerts
|

Tc-MDP bone scintigraphy in a case with sporodical tumoral calcinosis

Abstract: Tumoral calcinosis is an uncommon and benign condition characterized by the presence of large calcific soft tissue deposits occurring predominantly in a periarticular location. It generally occurs as a complication of renal dialysis or trauma, and is rarely seen in familial and sporadic cases. Bone scintigraphy is a sensitive method for diagnosing tumoral calcinosis. A 28-year-old female patient with a history of operation due to tumoral calcinosis located bilateral hips, referred to our department. She had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Bone scintigraphy has shown avid uptake of tracer in some of these lesions in adults. 7 Guveli et al 2 describe in their case report heterogeneous uptake of 99m Tc tracer into tumoral calcinosis in the lower limbs of a 28-year-old female. It is well recognized that tumoral calcinosis behaves differently in adults and is more likely to recur following excision, as in the case described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone scintigraphy has shown avid uptake of tracer in some of these lesions in adults. 7 Guveli et al 2 describe in their case report heterogeneous uptake of 99m Tc tracer into tumoral calcinosis in the lower limbs of a 28-year-old female. It is well recognized that tumoral calcinosis behaves differently in adults and is more likely to recur following excision, as in the case described.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The pathogenesis of the condition is the deposition of calcium crystals and salts in the soft tissues around large joints. 2 The most commonly affected large joints are the hips, pelvis, elbows and shoulders. Spinal involvement is rare.…”
Section: Discussionmentioning
confidence: 99%
“…While Tc-MDP bone scintigraphy has been used to in the past to diagnose sporadic case of tumor calcinosis with relapses,[ 7 ] to the best of the authors knowledge, there has not been case reports of de novo tumor calcinosis identified by whole bone scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Few reports have demonstrated the ability of Tc-99m MDP scintigraphy in detecting TC. [ 3 8 ] Proposed mechanism leading to increased extraosseous Tc-99m MDP uptake include extracellular fluid expansion, enhanced regional vascularity and permeability, diminished lymphatic or venous removal from the affected area, and elevated tissue calcium concentration. [ 9 ] Because of the advent of SPECT/CT, it is possible to localize exact site of tracer uptake and characterize the lesion to guide further management.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Few reports have demonstrated the ability of Tc-99m MDP scintigraphy in detecting TC. [ 3 ] Hybrid single-photon emission computed tomography/computed tomography (SPECT/CT) help in localizing uptake to the TC has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%